Geographical survey to explore minerals & clays economic-industrial deposits in different geomorphological units in Al-Qadisiyah Governorate using digital processing of Landsat 7,8 and Sentinel-2 – Iraq - Al-Gurairy, Ahmad Saied Yasien; Al-Edami, Rahman Rabat (Al-Adab Journal, 2023)
The exploration of rock layers with economic mineralization by remote sensing is a very important tool at present. Multisensor satellite visual data is a quick and inexpensive tool for mapping areas of geomorphological change and rock units associated with economic deposits such as high calcium limestone, gypsum, mineral clays, and silicic sands, which is of great economic importance. Multiple sources of spectral data derived from different remote sensing devices can be used to obtain detailed maps of a variety of economic minerals that can be used in various construction industries such as cement, gypsum, bricks, thermostone blocks, and so on. In this research, Landsat-7, Landsat-8, and Sentinel-2 sensors were used to survey and prospect for lime, gypsum, dolomite, sand, rocks containing a high percentage of iron oxides and mineral clays in the two main geomorphological units of Al-Qadisiyah Governorate, namely the unit, The Mesopotamian plain and desert shelf unit that forms part of the southern Iraqi desert. To process satellite, remote sensing data sets, band ratio operations, Arithmetic average of the bands, and Principal Component Analysis (PCA) techniques have been adopted and implemented to produce predictive mineral maps for a region. the study. The spatial distribution of carbonate minerals (lime and gypsum), sands, and mineral clays was determined, while no discoveries of dolomite or iron oxides were found in the target area. Metal predictive maps were created for the study area according to the results obtained. The results indicate that spectral data from multi-sensor remote sensing satellite datasets can be widely used to create remote sensing-based predictive maps for the exploration of exposure rocks, which contain important minerals for construction and other important economic industries in most regions around the world.